When are Capital Controls Effective? Evidence from Malaysia and Thailand - Juthathip Jongwanich; Maria Socorro Gochoco-Bautista; Jong-Wha Lee (Asian Development Bank (ADB), 2011)
This study examines the impact of capital controls using monthly information to construct higher-frequency, quarterly indexes for Malaysia during the period 2000–2008 and Thailand over the period 2000–2010 in a vector auto-regression model. The results show that restrictions in Thailand have no significant effect on inflows but are especially effective for outflows, particularly foreign direct investment. In Malaysia, capital relaxation tends to have a significant impact on inward foreign direct investment and portfolio inflows. Changes in capital account policies do not have a significant impact on the real exchange rate in Malaysia and Thailand.
hdl:11540/2040
Keywords: 330; Kapitalverkehrskontrolle; Kapitalmobilität; Auslandsinvestition; Portfolio-Investition; Kaufkraftparität; Malaysia; Thailand